2016
DOI: 10.1039/c6cc05376a
|View full text |Cite
|
Sign up to set email alerts
|

A six-step total synthesis of α-thujone and d6-α-thujone, enabling facile access to isotopically labelled metabolites

Abstract: The short synthesis of α-thujone relies on the functionalization of the readily available dimethylfulvene. Furthermore, the three main metabolites of the natural product were also synthesized. Since d-acetone can be used as a starting material, the route developed allows for the facile incorporation of isotopic labels which are required for detecting and quantifying trace amounts via GC/MS analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Finally, the hydroxy‐group‐directed Simmons–Smith cyclopropanation of 4 a under Furukawa conditions afforded bicycle 10 in 81 % yield as a single diastereomer. This reaction provides efficient access to analogues of thujone ( 11 ), an inhibitor of the γ‐aminobutyric acid A (GABAA) receptor …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the hydroxy‐group‐directed Simmons–Smith cyclopropanation of 4 a under Furukawa conditions afforded bicycle 10 in 81 % yield as a single diastereomer. This reaction provides efficient access to analogues of thujone ( 11 ), an inhibitor of the γ‐aminobutyric acid A (GABAA) receptor …”
Section: Methodsmentioning
confidence: 99%
“…Saponification of 3a (NaOH in ethanol, 50 8 8C) furnished carboxylic acid 8 (83 %), which was subsequently converted into the bridged bicycle 9 (73 %) under standard iodolactonization conditions.F inally,t he hydroxy-group-directed Simmons-Smith cyclopropanation of 4a under Furukawa conditions [26] afforded bicycle 10 in 81 %y ield as as ingle diastereomer.T his reaction provides efficient access to analogues of thujone (11), an inhibitor of the g-aminobutyric acid A(GABAA) receptor. [27] In summary,w eh ave developed ac opper-catalyzed enantioselective arylative desymmetrization of prochiral 4substituted or 4,4-disubstituted cyclopent-1-enes with diaryliodonium salts and found that the achiral counteranion of the iodonium salts had an important effect on the enantioselec-…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[57] The late-stage CÀHo xidations trategy also provedt ob ee ffective for the synthesis of hydroxylated main metabolites of monoterpenen aturalp roduct a-thujone (36), [60] with TFDO, as reported by Tiefenbacher and co-workersi n2 016 (Scheme 13). [61] Further,t he screening of severalo xidants showedt hat TFDO is the reagent of choice to carrying out the direct and clean conversion of 35 into 7-OH-a-thujone (36)i n 69 %y ield (Scheme 13). [61] For example, the use of ozonea ffords considerable overoxidation products,l owering the yield of the hydroxylated product 36 (47 %, Scheme 13).…”
Section: Site-selective Càhbond Oxyfunctionalization In Total Synthesmentioning
confidence: 99%
“…[61] Further,t he screening of severalo xidants showedt hat TFDO is the reagent of choice to carrying out the direct and clean conversion of 35 into 7-OH-a-thujone (36)i n 69 %y ield (Scheme 13). [61] For example, the use of ozonea ffords considerable overoxidation products,l owering the yield of the hydroxylated product 36 (47 %, Scheme 13). [62] The bryostatins,ac lass of highly oxygenatedm acrolides, are characterized by ar emarkable range of biological activities, [63] but prevalent is their ability to modulate the activity of protein kinase Cs imilar to that of phorbol( 16)a nd related natural products.…”
Section: Site-selective Càhbond Oxyfunctionalization In Total Synthesmentioning
confidence: 99%
“…Analytical studies might also benefit from labelled standards, as it was recently shown with the synthesis of deuterated thujone, or deuterated fatty acids . In these studies, multi‐ or fully deuterated compounds were prepared since quantification of trace amounts in complex mixture via GC/MS analysis required multiple labelling.…”
Section: Introductionmentioning
confidence: 99%